PENGEMBANGAN DANA HIBAH MASJID DARUL FALAH DESA BUNGBARUH KADUR PAMEKASAN DALAM MANAJEMEN ISLAM - Jailani Jailani; Moh. Faizar Rofiqi (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2022)
The purpose of this research is to see the financial management of mosques which is still not done in mosques. Literature study becomes a reference in collecting data on mosque financial management. This research is a descriptive qualitative research, in which the researcher observes and analyzes the existing data The role of mosques according to Al-Quran and Sunnah explains that mosques can be optimized as a place for community empowerment both from an economic, social, cultural and so on. The problems that arise in mosque institutions are regarding the ineffective management of mosque finances. Where there are still many flow of use of mosque cash only for the operational needs of the mosque without being developed for the empowerment of the community. Mosque cash must be divided into two allocations of funds, namely productive and consumptive funds. The allocation of these funds is intended so that the cash flow of the mosque can be used to improve the economy of the ummah. For this reason, the fatwa regarding the allocation of mosque funds must beimmediately relocated in order to strengthen the foundation of mosque financial management.